2021
DOI: 10.4236/aim.2021.119036
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Multi-Drug Resistant (MDR) and Extensively Drug Resistant (XDR) <i>Salmonella typhi</i> from Blood Samples of Patients Attending Tertiary Medical Centre in Dhaka City, Bangladesh

Abstract: Objective: Almost all year round occurrence of typhoid fever remains a major public health issue in Bangladesh. In recent years, there has been a significant rise in the prevalence of multi-drug resistance Salmonella typhi in Dhaka city. The major objective of this study was to observe the prevalence of multi-drug and Extended drug-resistant patterns of typhoidal Salmonella typhi among the patients attending a tertiary medical center by conventional culture and serologic test. Materials and Methods: Blood was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…12 Since the emergence of XDR typhoid fever in Karachi Sindh, Pakistan in 2016, there are increasing number of cases of drug resistant typhoid fever especially XDR typhoid documented by various studies. 13,14,15 Anwar T et al documented that majority of drug resistant typhoid fever cases in their study were of XDR typhoid and it was more common in males, younger age group (1-6 years), poor socioeconomic class and west district of Karachi. 16 Similarly, Zakir et al documented XDR typhoid fever cases to be more prevalent in their study with increased incidence in males and 0-10 year age group.…”
Section: Discussionmentioning
confidence: 92%
“…12 Since the emergence of XDR typhoid fever in Karachi Sindh, Pakistan in 2016, there are increasing number of cases of drug resistant typhoid fever especially XDR typhoid documented by various studies. 13,14,15 Anwar T et al documented that majority of drug resistant typhoid fever cases in their study were of XDR typhoid and it was more common in males, younger age group (1-6 years), poor socioeconomic class and west district of Karachi. 16 Similarly, Zakir et al documented XDR typhoid fever cases to be more prevalent in their study with increased incidence in males and 0-10 year age group.…”
Section: Discussionmentioning
confidence: 92%
“…S. typhi strains were resistant to macrolides, sulfonamides, penicillins, and cephalosporins. Ghurnee et al (2021) found that S. typhi was resistant to ciprofloxacin (99.52%) and nalidixic acid (81.60%). Farooq et al (2019) discovered S. typhi to be highly resistant to fluoroquinolones (ciprofloxacin and ofloxacin) at 84 and 87%, respectively, which agree with the findings of other studies that have reported high resistance from different regions of Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…Progressing to the more common use of azithromycin and meropenem will result in developing resistance against these antibiotics in near future, for the treatment of these XDR strains will accelerate the rise of azithromycin-resistant strains as well in the coming days. The XDR cases from Sindh especially Karachi, Pakistan highlight the rise of extensive cephalosporins resistance among Salmonella typhi strains, which demands the implication of a vital action plan before such strains become the usual phenotypes that will ultimately lead to treatment failure for typhoid fever with the available antimicrobial agents 23 .…”
Section: Discussionmentioning
confidence: 99%